The Law of Attraction and the Qur’anic Concept of Sustenance: A Comparative Theological and Epistemological Analysis - Siregar, Burhanuddin; Rahmayanti (TAFSE: Journal of Qur'anic Studies, 2026)
This article examines the theological and epistemological implications of adapting Law of Attraction (LoA) language within Islamic discourse on sustenance (rizq, divine provision). It focuses on Magnet Rezeki (Magnet of Sustenance) by Ustadz Nasrullah as a popular Islamic motivational text that connects sustenance with intention, gratitude, prayer, emotional discipline, and personal transformation. Using qualitative library research, the study combines thematic Qur’anic interpretation (tafsīr mawḍūʿī) with critical textual analysis of the book and relevant literature on LoA, Islamic theology, and popular spirituality. The analysis compares the two frameworks through three dimensions: the source of sustenance, the role of human agency, and the causal meaning assigned to spiritual and psychological practices. The findings indicate that Magnet Rezeki incorporates Islamic ethical concepts such as faith, supplication (duʿāʾ), gratitude (shukr), charitable giving (ṣadaqah), and effort, while also placing considerable emphasis on mental and spiritual self-management in the pursuit of sustenance. The book explicitly affirms Allah as the ultimate giver of provision and therefore cannot be equated straightforwardly with classical LoA. Nevertheless, theological ambiguity may arise when thoughts, emotions, affirmations, or spiritual practices appear to function as reliable mechanisms for producing material outcomes. The Qur’anic framework recognizes human effort, prayer, gratitude, charity, and piety as morally meaningful forms of obedience, while the realization, timing, and form of sustenance remain subject to Allah’s wisdom and decree. The article argues that contemporary motivational discourse may be accommodated within Islamic thought when it is understood as ethical and psychological encouragement rather than as an autonomous causal force that determines provision.